CARD and TM of MAVS of black carp play the key role in its self-association and antiviral ability. Issue 63 (April 2017) - Xiao, Jun; Yan, Chuanzhe; Zhou, Wei; Li, Jun; Wu, Hui; Chen, Tiansheng; Feng, Hao
Abstract: Mitochondrial antiviral signaling protein (MAVS) is an adaptor protein of the innate immune system of higher vertebrate. In this paper, the transcription profile of black carp MAVS (bcMAVS) in host cells in response to spring viremia of carp virus (SVCV) and grass carp reovirus (GCRV) infection was identified. EPC cells expressing bcMAVS possessed obviously enhanced antiviral activity against both SVCV and GCRV. Immunofluorescence (IF) staining data demonstrated that bcMAVS molecules were redistributed and formed aggregates on the mitochondria of EPC cells after virus infection. Co-immunoprecipitation (co-IP) assay in HEK293T cells demonstrated that bcMAVS proteins bound to each other, which suggested that this fish protein owned self-association in vivo . IF assay identified that the transmembrane (TM) domain of bcMAVS was crucial for its mitochondrial localization. Co-IP assays among bcMAVS mutants demonstrated that both N -terminal caspase recruitment domain (CARD) and TM domain were indispensible for dimerization of bcMAVS. It was interesting that Truncated-bcMAVS possessed much enhanced interferon-inducing activity and antiviral ability than wild type bcMAVS, which only contains CARD and TM. All the data generated in this study support the idea that oligomerization of bcMAVS on mitochondrion is crucial for the antiviral ability of bcMAVS, which is depend on both CARD and TM domain of this fish MAVS orthologue. Highlights: EPC cells overexpressing bcMAVS showed much increased anti-viral ability against both SVCV and GCRV. bcMAVS formed aggregates on mitochondria after viral infection and bcMAVS proteins bound to each other. Both CARD and TM domain of bcMAVS are crucial for its dimerization and antiviral ability in host innate immune response.